Parenteral nutrition support: Beyond gut feeling? Quality control study of parenteral nutrition practices in a Tertiary Care Hospital - Ramakrishnan, Nagarajan (Indian J Crit Care Med, 2016)
BACKGROUND: Enteral nutrition (EN) is preferred over parenteral nutrition (PN) in hospitalized patients based on International consensus guidelines. Practice patterns of PN in developing countries have not been documented. OBJECTIVES: To assess practice pattern and quality of PN support in a tertiary hospital setting in Chennai, India. METHODS: Retrospective record review of patients admitted between February 2010 and February 2012. RESULTS: About 351,008 patients were admitted to the hospital in the study period of whom 29,484 (8.4%) required nutritional support. About 70 patients (0.24%) received PN, of whom 54 (0.18%) received PN for at least three days. Common indications for PN were major gastrointestinal surgery (55.6%), intolerance to EN (25.9%), pancreatitis (5.6%), and gastrointestinal obstruction (3.7%). CONCLUSIONS: The proportion of patients receiving PN was very low. Quality issues were identified relating to appropriateness of indication and calories and proteins delivered. This study helps to introspect and improve the quality of nutrition support.